Preliminary study on the mechanism of Huangqi Decoction in treating slow transit constipation - Chen Huaxian; Yang Chaoxin; Xiao Guozhong; Zheng Yihui; Lei Mingyuan; Lin Hongcheng (结直肠肛门外科)
[Objectives] To explore the mechanism of Huangqi Decoction in the treatment of slow-transit constipation (STC) is based on network pharmacology, molecular docking technology and Western blot. [Methods] TCMSP and SymMap databases were used to screen the active ingredients and potential targets of Huangqi Decoction. STC-related targets were searched in GeneCards database and DisGeNET database, and the intersection targets of Huangqi Decoction and STC were obtained by drawing Venn diagram. Use Cytoscape software to construct the “herbal-active ingredients-target-disease” network diagram. The protein interaction (PPI) network diagram was constructed using STRING database and Cytoscape software and core targets were screened. The Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) functional enrichment analyses were performed for core targets using the clusterProfiler package. AutoDock Vina and Py-MOL were used for the molecular docking and the visualization of results. The expression levels of p65 and p-p65 in LS174T cells treated with lipopolysaccharide (LPS) + different concentrations of Huangqi Decoction were detected by Western blot. [Results] Through network pharmacological analysis, 174 active ingredients and 521 potential targets of Huangqi Decoction, 1,041 STC-related targets, 84 intersection targets of Huangqi Decoction and STC were obtained. The network diagram of “herbal-active ingredients-target-disease” showed that the top 5 active ingredients of Huangqi Decoction were acetic acid, quercetin, luteolin, kaempferol, and arachidonic acid. The core PPI network showed that the core targets of STC treated by Huangqi Decoction were IL6, IL1B, TNF, IL10, CCL2, ICAM1, TLR4, IFNG, IL1A and MMP9. Transcription-related targets RELA, RB1, NFKBIA, STAT1, RUNX1T1, PPARG, PPARA, RUNX2, PGR, SREBF1. The results of GO functional enrichment analysis showed that intersection genes were mainly concentrated in biological processes (BP) such as response to molecule of bacterial origin, regulation of inflammatory response, and positive regulation of cytokine production, molecular functions (MF) such as cytokine receptor binding and cytokine activity, and cell components (CC) such as membrane raft and membrane microdomain. KEGG functional enrichment analysis showed that intersection genes were mainly related to TNF, MAPK, PI3K-Akt, NF-κB and other signaling pathways. Molecular docking results showed that acetic acid, quercetin, luteolin, kaempferol, and arachidonic acid of Huangqi Decoction had good binding with p65 protein. Western blot results showed that the level of p-p65 protein in LPS treatment group was increased, and the level of p-p65 protein was decreased after three different concentrations of Huangqi Decoction. [Conclusion] The occurrence of STC is related to NF-κB signaling pathway, and Huangqi Decoction may inhibit NF-κB signaling pathway by reducing p-p65 protein level, and play a role in the treatment of STC.